Tingkat Keterampilan Bermain Bola Voli Pada Siswa Ekstrakurikuler Bola Voli Smp Negeri 8 Prabumulih - Angel Clarastri; Sukardi Sukardi; Taheri Akhbar (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This research aims to determine the level of volleyball playing skills among volleyball extracurricular students at SMP Negeri 8 Prabumulih. This type of research is quantitative descriptive research, using a survey method, namely collecting data regarding basic technical skills tests in volleyball at SMP Negeri 8 Prabumulih. The sample in this study was 21 men's volleyball extracurricular students at SMP Negeri 8 Prabumulih using a saturated sampling technique. The data collection technique uses the basic technical skills test method for playing volleyball. The data analysis technique uses a percentage formula. Based on the results of the research, it shows that the level of basic volleyball technical skills from the results of calculations using the T-Score formula in volleyball games for extracurricular volleyball students at SMP Negeri 8 Prabumulih obtained the number of basic bottom serve techniques with six opportunities to get the highest score was 26, the lowest score was 14 and an average of 19.33. The basic top passing technique using 60 seconds obtained the highest score of 25, the lowest score was 14, and the average was 17.76. The basic smash technique obtained the best points and times was 17 and 4.1 seconds, while the worst points and times were 7 and 12 seconds, and the average smash test results for points and times were 11.43 and 8.93.